(untitled) (Eurasian Journal of History, Geography and Economics, 2025)
The article discusses the current problems of creating a favorable investment climate in Uzbekistan, the main factors determining the investment climate, issues of reducing the country’s risks while increasing the attractiveness of the investment environment, and provides conclusions and recommendations.